Multi‐stage resource allocation in hybrid 25G‐EPON and LTE‐Advanced Pro FiWi networks for 5G systems. Issue 4 (1st July 2018) - Lagkas, Thomas; Sarigiannidis, Panagiotis; Bellavista, Paolo; Giannelli, Carlo
Abstract : The 5G vision is not restricted solely to the wireless domain and its challenging requirements cannot be fulfilled without the efficient integration of cutting‐edge technologies in all portions of the telecommunications infrastructure. The promoted architectures for next generation telecommunications systems involve high capacity network domains, which operate flexibly and seamlessly to offer full quality of experience to all types of subscribers. The proliferation of highly demanding multimedia services and the features of modern communication devices necessitate the development of end‐to‐end schemes which can efficiently distribute large amount of network resources anywhere and whenever needed. This study introduces a new resource allocation scheme for cutting‐edge fibre‐wireless networks is introduced that can be applied in the fronthaul portion of 5G‐enabled architectures. The adopted technologies are the forthcoming 25G‐Ethernet Passive Optical Network (EPON) for the optical domain and the 5G‐ready long‐term evolution ‐Advanced Pro for the wireless domain. The proposed scheme performs allocation decisions based on the outcome of an adjustable multi‐stage optimisation problem. The optimisation factors are directly related to the major considerations in bandwidth distribution, namely priority‐based traffic differentiation, power awareness, and fairness provision. The conducted evaluations prove that this approach is able to ensure high efficiency in network operations.